The Grid: Blueprint for a New Computing Infrastructure - Foster (Ian); Kesselman (Carl) ("17-A / 1, Main Ring RoadLajpat Nagar IV,New Delhi,New Delhi,India-110 024", 2006)
Distributed Computing
22.5
Keywords: Distributed Computing